2014
DOI: 10.1073/pnas.1209249111
|View full text |Cite
|
Sign up to set email alerts
|

Loss of BMAL1 in ovarian steroidogenic cells results in implantation failure in female mice

Abstract: The circadian clock plays a significant role in many aspects of female reproductive biology, including estrous cycling, ovulation, embryonic implantation, onset of puberty, and parturition. In an effort to link cell-specific circadian clocks to their specific roles in female reproduction, we used the promoter that controls expression of Steroidogenic Factor-1 (SF1) to drive Cre-recombinase-mediated deletion of the brain muscle arnt-like 1 (Bmal1) gene, known to encode an essential component of the circadian cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 40 publications
2
84
0
2
Order By: Relevance
“…Thus, any disorder that alters or abolishes normal patterns of hormone secretion might be expected to have significant detrimental effects on circadian organization. The inverse relationship has already been established; that is, mutations affecting the circadian clock have been shown to alter steroid hormone synthesis and secretion [15,59]. Our results provide further evidence that internal circadian misalignment may be a critical factor in the etiology of complex disorders affecting both reproduction and metabolism.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Thus, any disorder that alters or abolishes normal patterns of hormone secretion might be expected to have significant detrimental effects on circadian organization. The inverse relationship has already been established; that is, mutations affecting the circadian clock have been shown to alter steroid hormone synthesis and secretion [15,59]. Our results provide further evidence that internal circadian misalignment may be a critical factor in the etiology of complex disorders affecting both reproduction and metabolism.…”
Section: Discussionsupporting
confidence: 54%
“…It has been reported that the ovarian clock regulates the timing of sensitivity to endocrine signals, including the rhythmic secretion of gonadotropins [14]. Others have linked circadian clock function to reproductive physiology, with particular emphasis on steroid hormone synthesis [15,16]. Mutations that suppress clock function have dramatic impacts on fertility, including irregular LH secretion, abnormal cycles and implantation failure [17,18].…”
Section: Introductionmentioning
confidence: 98%
“…Recent genetic studies strongly suggest an important role of Bmal1 in mammalian reproductive physiology (8,38,46). Bmal1 Ϫ/Ϫ mice are infertile with implantation failure and impaired steroidogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Further, bmal1-/-mice have abnormally low levels of progesterone secretion due to reduced StAR expression (Ratajczak et al, 2009). It was recently reported that mice with a conditional knockout of the BMAL1 locus in steroidogenic cells (steroidogenicfactor 1-Cre; Bmal1flx/flx) show severe deficits in implantation success and compromised progesterone secretion (Liu et al, 2014). It was recently reported that mice with a conditional knockout of the BMAL1 locus in steroidogenic cells (steroidogenicfactor 1-Cre; Bmal1flx/flx) show severe deficits in implantation success and compromised progesterone secretion (Liu et al, 2014).…”
Section: Circadian Clock In the Ovary: Role In Steroidogenesismentioning
confidence: 99%